Bone mineral loss in young women with amenorrhoea. Issue 6755 (6th October 1990) - Davies, M C; Hall, M L; Jacobs, H S
Abstract : OBJECTIVE–To examine the impact of amenorrhoea on bone mineral density in women of reproductive age. DESIGN–Cross sectional study of 200 amenorrhoeic women compared with normally menstruating controls. SETTING–Teaching hospital outpatient clinic specialising in reproductive medicine. SUBJECTS–200 Women aged 16-40 with a past or current history of amenorrhoea from various causes and of a median duration of three years, and a control group of 57 age matched normal volunteers with no history of menstrual disorder. MAIN OUTCOME MEASURE–Bone mineral density in the lumbar spine (L1-L4) as measured by dual energy x ray absorptiometry. RESULTS–The amenorrhoeic group showed a mean reduction in bone mineral density of 15% (95% confidence interval 12% to 18%) as compared with controls (mean bone mineral density 0.89 (SD 0.12) g/cm2 v 1.05 (0.09) g/cm2 in controls). Bone loss was related to the duration of amenorrhoea and the severity of oestrogen deficiency rather than to the underlying diagnosis. Patients with a history of fracture had significantly lower bone density than those without a history of fracture. Ten patients had suffered an apparently atraumatic fracture. CONCLUSIONS–Amenorrhoea in young women should be investigated and treated to prevent bone mineral loss. Menopausal women with a past history of amenorrhoea should be considered to be at high risk of osteoporosis.